The Economics and Politics of Trade Policy: An Empirical Analysis of ITC Decision Making - Wendy L. Hansen; Thomas J. Prusa (Rutgers University, Department of Economics, 1996)
We study the determinants of trade policy decisions focusing specifically on antidumping and countervailing duty statutes administered by the International Trade Commission (ITC). Using detailed industry, import, and political pressure data we model ITC decision making, weighing the relative impact of economic and political factors in predicting policy outcomes. We find the ITC's decision making is significantly influenced by both economic and political factors. However, because an industry has much greater ability to create political pressure than induce economic injury, our results highlight the strategic importance of oversight representation and PAC contributions in an industry's bid for protection.
Keywords: F1; 330; ITC